Stabilność adaptacji potomstwa buka zwyczajnego Fagus sylvatica L. po pięciu latach wzrostu - Jaźwiński, Jakub; banach, Jacek; Skrzyszewska, Kinga; Strejczek-Jaźwińska, Paulina (Leśne Prace Badawcze, 2019)
This study was focused on the evaluation of beech adaptation on test plots in the Góra Śląska and Świebodzin Forest Districts. For this purpose, we examined offspring from seed stands of beech growing in the Regional Directorates of State Forests in Szczecin, Szczecinek, Piła, Zielona Góra and Poznań, which were brought to both test plots. The aim was to determine the adaptive response of the offspring from these stands after five years of growth with respect to the changed environmental conditions compared to the site of origin. Our analysis revealed a relatively low survival rate which was 60.8% and 72.2% in Góra Śląska and Świebodzin respectively. Interestingly, beeches grown on the plot in Góra Śląska were about 40% higher than those grown in Świebodzin (77.6 cm). The trees from both plots were significantly different from each other in terms of the analyzed features and a significant interaction was observed between test plot and site of origin. However, the variability in the adaptive response of the seedlings was large. Using a regression coefficient and the average height value, we determined the seedlings stability, which indicated high quality in offspring from the beech stand in the Łopuchówko Forest District (Buczyna forest range, sub-compartment 95n) and a high degree of adaptation to growth in adverse environmental conditions. Our results also indicate a low survival rate and reduced height of beech offspring from commercial seed stands (local standard).